2021
DOI: 10.1007/s11606-021-06913-3
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Risk Perceptions During the COVID-19 Pandemic Reported by Recently Hospitalized Participants in a Smoking Cessation Trial

Abstract: Background Cigarette smoking is a risk factor for severe COVID-19 disease. Understanding smokers’ responses to the pandemic will help assess its public health impact and inform future public health and provider messages to smokers. Objective To assess risk perceptions and change in tobacco use among current and former smokers during the COVID-19 pandemic. Design Cross-sectional survey conducted in May–July 2020 (55% response rate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 25 publications
5
28
0
1
Order By: Relevance
“…Intervention development will likely need to consider how smokers perceived the risk for COVID-19. In our sample, the vast majority of participants believed that COVID-19 would be more severe for smokers, consistent with another study in the USA [66]. This perception remained stable from March to July, perhaps reflecting inconsistent media coverage of the relationship between COVID-19 and smoking.…”
Section: Discussionsupporting
confidence: 86%
“…Intervention development will likely need to consider how smokers perceived the risk for COVID-19. In our sample, the vast majority of participants believed that COVID-19 would be more severe for smokers, consistent with another study in the USA [66]. This perception remained stable from March to July, perhaps reflecting inconsistent media coverage of the relationship between COVID-19 and smoking.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that a great majority of respondents, both men and women, agreed that smoking increases the risk of getting infected with the COVID-19 virus ( Figure 1 ). Similar results were obtained in a study by Rigotti et al In this research conducted among 694 current and daily smokers who were also COVID-19 patients, 68% of them believed that smoking is connected with higher risk of infection [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…A possible explanation is that young people are less competent in identifying health risks and tend to judge themselves as having a minimal chance of developing negative health outcomes because of their better physical health and the remoteness of the potential outcomes [ 27 ]. Rigotti et al [ 28 ] found that perceived vulnerability to COVID-19 is a key factor that influences smokers’ motivation to quit smoking, with those perceiving a higher risk of infection being more motivated to quit. Because young smokers perceive a lower level of vulnerability, it is understandable that a majority of them opted to maintain their daily cigarette consumption during COVID-19, as shown in our previous quantitative study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%